1995
DOI: 10.1063/1.360229
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy and x-ray diffraction of PbTiO3 thin film

Abstract: A PbTiO3 thin film prepared on silicon substrate by sol-gel technique has been studied by micro-Raman spectroscopy and x-ray diffraction (XRD). The spectra, in comparison to the single crystal work, show high background in the low frequency region and Raman lines are broader, thus revealing the polycrystalline nature of the film. The frequencies of the Raman bands in the film are clearly shifted to lower frequencies compared to the corresponding ones in the single crystal or powder forms. This phenomenon is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…The obtained temperature dependences of the soft mode frequencies and the damping (Figs. 1 and 2) (the damping is related to the width of the half-maximum for the Raman scattering lines) could explain the experimental results of Raman scattering from ferroelectric thin films [14,16,17]: a) the Raman frequencies for the thin film remarkabely shift to low frequencies compared with those for the bulk; b) the Raman lines of the thin film are broaded in comparison with those for the bulk; c) the line shapes of the film become broad as the temperature approaches T c .…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The obtained temperature dependences of the soft mode frequencies and the damping (Figs. 1 and 2) (the damping is related to the width of the half-maximum for the Raman scattering lines) could explain the experimental results of Raman scattering from ferroelectric thin films [14,16,17]: a) the Raman frequencies for the thin film remarkabely shift to low frequencies compared with those for the bulk; b) the Raman lines of the thin film are broaded in comparison with those for the bulk; c) the line shapes of the film become broad as the temperature approaches T c .…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…Recently, several research groups carried out Raman scattering studies to characterize the ferroelectric thin films and showed that all transverse optical (TO) phonons tended to depart from the corresponding positions of the bulk single crystal, implying that differences might exist between thin films and bulk single crystals [13][14][15][16][17][18]. Using Raman spectroscopy the temperature dependence of the phonon modes for thin ferroelectric films of PbTiO 3 is discussed by Taguchi et al [16] and Fu et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the stress, the soft-mode wavenumber at each thickness was compared with the hydrostatic pressure dependence of the soft-mode wavenumber in single-crystal PT. 33 We have calculated the lattice constants of PT in all the films from x-ray data and compared them with the hydrostatic pressure dependence of the lattice parameters in PT at room temperature. 40,41 From both methods, it was found that PT films are stressed about 1.15-2.4 GPa, depending upon film thickness.…”
Section: Thickness Effect In Pbtio 3 Thin Filmsmentioning
confidence: 99%
“…In the past, optical fluorescence [12], X-ray diffraction (XRD) [13], wafer curvature measurements [14], cantilever beam deflection [15], laser reflectance [16], and Raman spectroscopy [17]- [24] have been used for stress analysis of ferroelectric materials. Among them, XRD and Raman spectroscopy are the most popular techniques, as they are powerful tools for nondestructive investigation of structure.…”
Section: Introductionmentioning
confidence: 99%